Reactions between palm stearin alkyds with high carboxylic acid content and epoxidised natural rubber / Khong Yoke Kum - Khong, Yoke Kum (2014)

(untitled)
Vulcanisation serves as a chemical process to transform weak and permanently deformable rubber into vulcanised rubber with ultimate elastic performance. Crosslinking of rubber using environment friendly crosslinker without any toxic additive offers a wide range of potential applications. In this work, self-vulcanisable rubber blend that utilises reaction between epoxidised natural rubber with 50 mol % of epoxidation (ENR50) and palm stearin alkyd at ambient temperature has been developed. Palm stearin alkyds were used as green crosslinkers in epoxidised natural rubber. The first alkyd (AlkydCO) was formulated with excess hydroxyl groups and low level of carboxyl groups, reflected from its hydroxyl value (148.5 mg KOH/g alkyd), and acid value (16.7 mg KOH/ g alkyd). AlkydCO was then utilised to produce modified alkyds with higher amounts of carboxyl groups. AlkydMA1 and AlkydMA2 were prepared through half ester formation between hydroxyl groups in AlkydCO with maleic anhydride (MA) at controlled reaction temperature, while AlkydPA1 was prepared from phthalic anhydride (PA). Incorporation of acid anhydride into AlkydCO has resulted in the increase in acid values of AlkydMA1 and AlkydMA2 to 44.0 and 68.7 mg KOH/ g alkyd respectively, while AlkydPA1 recorded acid value of 46.0 mg KOH/ g alkyd. These alkyds were then blended with ENR50 through solvent casting technique and thin films of the blend were analysed by FTIR, 1H-NMR, DSC and TGA. The occurrence of crosslinking in the rubber is in good agreement with the gel content results, where ENR50/Alkyd blends able to resist dissolution and appear as gel in toluene. Individually, ENR50 and alkyd is completely soluble in toluene. The carboxylic acid side chain in alkyd is responsible for the crosslinking with epoxide group in ENR50. AlkydMA2 which has higher density of carboxyl group produces blend with higher percentage of gel, higher crosslink density and higher Tg iv than ENR50/AlkydMA1 blend. At equivalent level of carboxyl content, the structure of the pendant –COOH groups at the alkyd was found to affect the crosslinking reaction as well. AlkydMA1 with pendant –OOC-CH=CH-COOH groups are able to produce blend with higher amount of gel insoluble in toluene and better thermal resistance as compared to ENR50/AlkydPA1 blend where the acid side chain of carboxylic acid in the alkyd comprised of–OOC-Ph-COOH (where Ph = aromatic ring). In the later part of this work, extent of crosslinking in the ENR50/Alkyd blend was enhanced via incorporation of ultraviolet (UV) curing technology. Benzophenone which acts as UV photoinitiator was introduced into the system, followed by irradiating the blend using UV light. UV irradiation has induced formation of crosslinked structure involving -C=C- in the system. FTIR peak absorbance at 835 cm-1 which corresponds to -C=C- group of the isoprene unit in ENR50 has reduced significantly upon UV irradiation. Further approach was taken to enhance crosslinking in the system by incorporating trimethylolpropanetriacrylate (TMPTA). Likewise, crosslink density in the blend has improved where the product is able to better resist dissolution when immersed in toluene.